Contradictory Results in Microbiome Science Exemplified by Recent Drosophila Research - Angela E. Douglas (American Society for Microbiology, 2018)
ABSTRACT The bacterium Lactobacillus plantarum is prevalent in animal guts and is widely regarded as beneficial and probiotic. D. Fast et al. (mBio 9:e01114-18, 2018, https://doi.org/10.1128/mBio.01114-18) make the surprising discovery that L. plantarum reduces the life span of Drosophila melanogaster and link this effect with the loss and weakened proliferation of stem cells in the Drosophila gut. These results are apparently at odds with published evidence for beneficial effects of L. plantarum, especially promoting high developmental rates and stimulating stem cell proliferation in young Drosophila. The among-study discrepancies highlight the context dependence of many effects of gut microbes on host health, likely influenced by host age and genotype, variation among bacterial strains, and diet. The diversity of results offers an opportunity to elucidate a fundamental mechanism(s) and the circumstances that dictate whether gut bacteria have positive or negative effects on host health. These studies also reinforce the value of Drosophila as an emerging model system for probiotic science.